PESANTREN AND THE PRESERVATION OF ISLAM NUSANTARA - Edi Susanto; Mashur Abadi (Karsa: Journal of Social and Islamic Culture, 2015)
This article describes the background of the rise of an Indonesian moderate Islamic understanding in the midst of a trans-national Islamic movement with the scriptural-puritanical in it’s character which spread out pervasively in the country; and this new Islamic model is intolerant to local traditions.  Meanwhile, historically, Islam Nusantara has been deeply rooted among the Moslems in archipelago, and this traditional-moderate Islam has been developed by Wali-songo. Islam Nusantara is accommodative to the local cultures and traditions. It produces a moderate and tolerant model of Islam. This article also describes the role of pesantren in protecting the heritages of Islam Nusantara. Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i2.718